Changes in the kinematic and kinetic profile of handcycling propulsion due to increasing workloads - Quittmann, O. J.; Meskemper, J.; Abel, T.; Albracht, K.; Strüder, H. (ISBS Proceedings Archive (Michigan), 2017)
The aim of this study was to examine changes in handcycling propulsion kinematics and kinetics due to increasing workloads. Twelve non-disabled male triathletes without handcycling experience performed a familiarisation protocol and an incremental step test in a recumbent racing handcycle that was attached to an ergometer. During the incremental test, the tangential crank kinetics, 3D joint kinematics, blood lactate and the rate of perceived exertion (local and global) were identified. The participants showed a significant increase in shoulder internal rotation and abduction and a decrease in elbow flexion and retroversion. Future studies should expand the test spectrum, consider the examination of muscle activation patterns (MAP) and replicate the study with elite handcyclists.